Modelling the Transformation of Agricultural Program Teaching and Learning into Technology Integration - Sephokgole, Ramongwane Daniel; Makgato, Moses; Khoza, Sammy (Journal of Education Technology, 2024)
The world is currently experiencing transformation in most areas, including in education. The teaching and learning of agricultural programmes ought to be modelled and aligned with transformation. The shift from traditional classroom teaching and learning requires support to train agriculture with technology integration. Therefore, the aim of this study is to analyze the transformation of the teaching and learning of agricultural programmes using technology. This study utilised a qualitative research method. There were 20 lecturers from three Technical and Vocational Education and Training (TVET) college campuses that were involved in this study. The findings revealed that transforming agricultural programmes to fully integrate technology is hampered by a lack of resources, equipment, and infrastructure. Teaching and learning support with resources and tools to acclimate to learning agriculture with technology integration is required. The study underscored the need for and the importance of providing support to institutions that are struggling to acquire teaching and learning resources, equipment, and infrastructure to implement the integration of technology. These findings emphasise the need to provide support for technical resources, equipment, and infrastructure to enhance the integration of technology. The research findings led to the development of a conceptual model for technology integration in TVET agricultural education. The key interrelated features that can be used to improve the support of technology integration in TVET colleges are clearly stipulated in the model.